Groups, combinatorics & geometry : Durham, 1990 - Liebeck, M. W. (Martin W.), 1954-; Saxl, J. (Jan), 1948- (London Mathematical Society lecture note series, 1992)
Since the classification of finite simple groups was announced in 1980 the subject has continued to expand opening many new areas of research. This volume contains a collection of papers, both survey and research, arising from the 1990 Durham conference in which the excellent progress of the decade was surveyed and new goals considered. The material is divided into eight sections: sporadic groups; moonshine; local and geometric methods in group theory; geometries and related groups; finite and algebraic groups of Lie type; finite permutation groups; further aspects of Lie groups; related topics. The list of contributors is impressive and the subjects covered include many of the fascinating developments in group theory that have occurred in recent years. It will be an invaluable document for mathematicians working in group theory, combinatorics and geometry.